A review of the Famatinian Ordovician magmatism in southern South America: Evidence of lithosphere reworking and continental subduction in the early proto-Andean margin of Gondwana - Rapela, Carlos Washington (2018)
Along the proto-Pacific margin of Gondwana, from Venezuela to northeastern Patagonia, the Early–Middle Ordovician Famatinian orogeny was the first orogenic event following assembly of the supercontinent. Previous isotope studies of the igneous and (meta-)sedimentary rocks of southwestern Gondwana yield ambiguous implications for the role of juvenile mantle addition during the early crustal growth at the supercontinental margin. To interpret the geological and tectonic evolution of the orogen and the magma sources in different episodes we look at evidence from a large area of southern South America, including the 700 × 600 km type sector of the orogen in the Sierras Pampeanas (27°–33°S), the Precordillera, and northeastern Patagonia. Previous geological, geochemical and geochronological results are reviewed together with new U—Pb SHRIMP crystallization ages, 177Hf/176Hf and 18O/16O data for dated zircon, and whole-rock Sr and Nd isotope compositions. Four geological domains are recognized in the Sierras Pampeanas (Western, Central, Eastern and Foreland Famatinian domains). Magmatism is mostly restricted to the interval 463 ± 4 to 486 ± 7 Ma, with the most intense period of emplacement between 468 and 472 Ma constituting a magmatic flare-up. Granitoid emplacement in both northeastern Patagonia and the Cordon de Lila (Puna Altiplano, Chile) was effectively synchronous with that in the Sierras Pampeanas, defining a continuous belt. Combined geochemical and isotopic data (whole-rock Sr, Nd; Hf, O in zircon) indicate that the source of calcic metaluminous suites is the subcontinental lithosphere – both mantle and mafic lower crust – with variable contamination by the Early Paleozoic metasedimentary country rocks. The lithospheric mantle involved is assumed to underlie the outcropping 1330–1030 Ma age basement of the Western Domain, which exhibits tectonic characteristics of active continental margin in the north and oceanic arc-back arc in the south. The latter sector is the potential source of some minor Famatinian igneous rocks with less evolved isotopic compositions, although a restricted asthenospheric addition cannot be discarded in this case. Minor peraluminous granites are spatially associated with the metaluminous sequence, but major highly-peraluminous batholiths occur on the eastern flank of the Central Domain. Field relations and geochemical/isotopic evidence indicate that the most obvious source of these crustal melts was the very thick post-early Cambrian metasedimentary sequence comprising the host country rocks. Episodic tectono-magmatic evolution of the Famatinian magmatic belt in two overlapping stages is invoked to explain different characteristics in the four recognized domains in the type sector: • ca. 474–486? Ma, roll-back stage. This is a mainly extensional interval involving asthenospheric upwelling and thinning of the subcontinental mantle; full development of the marine ensialic basins and early emplacement of both metaluminous granites and highly-peraluminous batholiths in the Central and Eastern Famatinian domains. Trondhjemite plutons with an adakitic signature were emplaced in the Foreland Domain• ca. 468–472 Ma, slab break-off stage. Steepening of the oceanic slab and arc migration to the southwest ended with slab break-off due to subduction of continental crust during continental collision with the Precordillera terrane. This stage produced voluminous metaluminous magmatism at the western edge of the Central Domain (the flare-up episode), K-bentonites in the Precordillera, leucogranites in the Western Domain and scattered metaluminous and peraluminous plutons in all Famatinian domains.Both slab roll-back and break-off stages developed during a high-T regime typical of hot orogens. Although asthenospheric mantle was a necessary heat source for lithospheric melting, its material contribution to the growth of Early Paleozoic crust was apparently very minor. Recycling of Mesoproterozoic lithosphere, including the subcontinental mantle, coupled with crustal melting of Early Paleozoic metasedimentary sequences, accounts for most Famatinian magmatism. Comparable results from the Central Andes and East Antarctica confirm that the early stages of the Terra Australis orogen in SW Gondwana were dominated by lithospheric reworking processes.